MATHEMATICAL MODELING OF HEAT TRANSFER IN THE HEATING FURNACE WITH A SLEEK HEARTH BOTTOM - D. V. Mendelev; I. A. Trusova; P. E. Ratnikov; M. L. German (Литьë и металлургия)
Results of mathematical modeling of heat exchange processes in transfer heating furnaces of continuous operation type of machine-building production are given.